Dance photography : surpassing the reality of movements. - Tan, Selina Hui Juan. (2011)
This paper seeks to introduce dance photography as a product of the final hyperreal, making a clean break from the ‘conventional’ genre of photography that strives to capture the reality of movements. In order for dance photography to simulate apparent qualities belonging to pure dance movements, the photographer has to consciously imbue illusion into his works, thereby surpassing the reality of motion through the imagination of the viewer.